The mitochondrial genome of Smerinthus planus (Lepidoptera: Sphingidae) and its comparative analysis with other Lepidoptera species - Wu, Lingling; Jiang, Xiaoli; Xie, Fengjiao; Kausar, Saima; Liang, Dan; Wei, Guoqing; Zhu, Baojian; Wang, Lei; Liu, Chaoliang; Qian, Cen (Zootaxa, 2020)
In the present study, the complete mitochondrial genome of Smerinthus planus Walker (Lepidoptera: Sphingidae) was sequenced and analyzed to add additional traits for expanding our knowledge on systematics and phylogenetics of world-wide studied Sphingidae moths. The mitochondrial genome is a circular double-stranded DNA molecule, 15368 bp in size. It includes 13 protein-coding genes (PCGs), two ribosomal RNA (rRNA) genes, twenty-two transfer RNA (tRNA) genes, and an adenine (A) + thymine (T) rich region. All the PCGs start with the typical ATN start codons, except for the nad5 gene, which initiates with TTA. The codon usage analysis revealed that Phe, Ile, Lys, Leu, Asn, and Tys were the most common amino acids, while Cys and Trp were least common. Among the 13 PCGs, nine genes harbor the complete termination codon TAA, whereas the remaining four genes (nad1, cob, nad4, and nad3) terminate with TAG. The A+T rich region of S. planus is 318 bp. This region displays the highest A+T rich content, accounting for 91.50%, with both AT skew (-0.09) and GC skew (-0.26) are negative. Like other Lepidopterans, the A+T-rich region of the S. planus also contains some conserved regions, including the motif ‘ATAGA’ followed by an 18 bp poly-T stretch, a microsatellite-like (AT)8 and a poly-A element. Phylogenetic relationships, based on nucleotide sequences from the genomes of 31 species, confirmed that S. planus belong to the Sphingidae family. This study is aimed to improve the mitochondrial genome database of moths and provide valuable information for studying the genetic evolution and phylogeny of Lepidopteran species.